1988
DOI: 10.1073/pnas.85.12.4431
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the 5' flanking region of the beta-globin gene in African sickle cell anemia patients: further evidence for three origins of the sickle cell mutation in Africa.

Abstract: Haplotype analysis of the ,3-globin gene cluster shows two regions of DNA characterized by nonrandom association of restriction site polymorphisms. These regions are separated by a variable segment containing the repeated sequences (ATTTT). and (AT)XTy, which might be involved in recombinational events. Studies of haplotypes linked to the sickle cell gene in Africa provide strong argument for three origins of the mutation: Benin, Senegal, and the Central African Republic. Nevertheless, the haplotype determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
4

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 23 publications
1
31
0
4
Order By: Relevance
“…The frequency of sickle cell allele in hemoglobin (HbS) varies greatly, globally and within Africa, in relation to the historical endemicity of malaria. Recent evidence suggests that the allele arose independently multiple times in history, as HbS is found on several different haplotype backgrounds (55,56). The survival advantage conferred by the HbS allele (a dominant trait) caused it to increase in frequency until the recessive disease became common.…”
Section: The Origins Of Apol1 Renal Risk Variantsmentioning
confidence: 99%
“…The frequency of sickle cell allele in hemoglobin (HbS) varies greatly, globally and within Africa, in relation to the historical endemicity of malaria. Recent evidence suggests that the allele arose independently multiple times in history, as HbS is found on several different haplotype backgrounds (55,56). The survival advantage conferred by the HbS allele (a dominant trait) caused it to increase in frequency until the recessive disease became common.…”
Section: The Origins Of Apol1 Renal Risk Variantsmentioning
confidence: 99%
“…Characterization of the DNA structure flanking the b-globin locus of HbS suggests that the mutation has arisen on at least three independent occasions in the African continent, referred to as b-globin haplotypes and named after the areas where they were first described: Benin, Senegal, and Central African Republic or Bantu (Pagnier et al 1984;Nagel et al 1985;Chebloune et al 1988). The HbC trait is believed to be a relatively recent mutation limited to West Africa where it occurs at high frequencies (.20%) in central Ghana and Burkina Faso, in only 2% in Nigeria, and does not occur, except in peoples of West African origin, in East and Central Africa.…”
Section: Geography Of Sickle Cell Disease Populations Of African Originmentioning
confidence: 99%
“…There are differences in the clinical severity of SCA among the haplotypes, with the Indian-Arabo (hereafter referred to as the Indian haplotype) being the mildest and the Bantu being the most severely affected (35). A sequence polymorphism within the Ϫ530 bp binding site for BP1 in silencer I is also in linkage disequilibrium with these five SCA haplotypes (6). Using competition electrophoretic mobility shift assays (EMSAs), it was found that BP1 binds five to six times more tightly to the Indian haplotype sequence than to the normal sequence (2,15,47).…”
mentioning
confidence: 99%